TAFIáº’ LEARNING MANAGEMENT IN IMPROVING STUDENTS 'INTERESTS IN MEMORING THE ALQURAN IN YAYASAN TAHFIDZUL QURAN AL-FAWWAZ MEDAN - Candra Wijaya; M Fajri Syahroni Siregar; Muhammad Ruslan; Syahrul Holid; Roslaeni Roslaeni (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study aims to determine the management of learning Taá¸¥fiáº“ Alquran which includes planning and organizing learning, implementing the learning and evaluating learning. This research is qualitative with a case study model. The collection method uses observation, interviews and also does documentation. The results showed that: (1) Management of learning Taá¸¥fiáº“ Alquran in increasing interest in memorizing the Koran at the Taá¸¥fiáº“ Al-Fawwaz Foundation includes: (a) learning planning consisting of memorization targets, learning objectives, learning programs, time allocation to learning tools, (b) learning that has a teaching team organization division and students are also grouped, (c) the implementation of learning which consists of learning activities and learning motivation, (d) learning evaluation.Â